The Russian Parliament : institutional evolution in a transitional regime, 1989-1999 - Remington, Thomas F., 1948- (Yale University Press, 2001)
From the first free elections in post-Soviet Russia in 1989 to the end of the Yeltsin period in 1999, Russia's parliament was the site of great political upheavals. Conflicts between communists and reformers generated constant turmoil, and twice parliamentary institutions broke down in violence. This book offers the first full account of the inaugural decade of Russia's parliament. Thomas F. Remington, a leading scholar of Russian politics, describes in unique detail the Gorbachev-era parliament of 1989-91, the interim parliament of 1990-93, and the current Federal Assembly. Focusing particularly on the emergence of parliamentary parties and bicameralism, Remington explores how the organization of the Russian parliament changed, why some changes failed while others were accepted, and why the current parliament is more effective and viable than its predecessors. He links the story of parliamentary evolution in Russia to contemporary theories of institutional development and concludes that, notwithstanding the turbulence of Russia's first postcommunist decade, parliament has served as a stabilizing influence in Russian political life.